Liquidity Potential Analysis of Sharia Banks Using Stock-Based and Flow-Based Methods - Aqidah Asri Suwarsi; Syakir Jamaluddin; Diyah Fajri Anggraini; Anisatun Anggraeni (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. Bank liquidity is adequate if the bank has sufficient funds when depositors withdraw them. The bank’s inability to meet its depositors’ rights will negatively affect public confidence and bank profitability. This study is to identify the potential liquidity risk of Islamic Commercial Banks in Indonesia using the Stock-Based and Flow-Based Methods based on OJK regulation. The assessment of the potential for liquidity risk using the stock-based method and the weight of the inherent risk value results in the statement risk level for each Islamic commercial Bank, ranging from 2.25 (low) to 2.85 (moderate). The flow-based method results in a negative liquidity gap. This research finds that bank liquidity has no significant impact on its profitability. The research provides direction for Islamic commercial banks in measuring liquidity risk so that the bank can formulate strategies for risk mitigation and control to avoid financial distress. Keywords: Flow-Based, Liquidity, Profitability, Risk Management, Stock-Based Abstrak. Likuiditas bank dikatakan baik apabila bank mampu memenuhi dana yang dibutuhkan saat deposan melakukan penarikan. Namun, jika bank tidak mampu memenuhi dana yang dibutuhkan oleh para deposan, maka tingkat kepercayaan masyarakat bisa berkurang dan memengaruhi profitabilitas bank. Penelitian ini mengidentifikasi potensi resiko likuiditas Bank Umum Syariah di Indonesia dengan Metode Stock-  Based dan Flow-Based, berdasarkan peraturan OJK. Penilaian potensi terjadinya risiko likuiditas dengan menggunakan metode stock-based dan bobot nilai risiko inheren memperoleh hasil tingkat risiko pada masing-masing bank umum syariah yang berkisar antara 2,55 (moderate) sampai dengan 3,15 (moderate). Metode flow-based, secara keseluruhan, menghasilkan gap likuiditas negatif. Dalam penelitian ini, tidak terdapat pengaruh likuiditas bank terhadap profitabilitas. Penelitian ini bermanfaat untuk memberikan arahan kepada Bank  Umum Syariah dalam mengukur Risiko Likuiditas sehingga Bank mampu merumuskan strategi untuk mitigasi dan pengendalian risiko untuk menghindari kondisi Financial Distress.Kata kunci: Flow-Based, Likuiditas, Manajemen Risiko, Profitabilitas, Stock-Based